Fibrin-type firbinoid in human placenta: a stereological analysis of its association with intervillous volume and villous surface area - Mayhew, Terry M. (Image analysis and stereology, 2001)
Stereological methods were used to examine fibrin-type fibrinoid deposition inthe intervillous spaces of human placentas collected during gestation (12-41weeks) and from term pregnancies at low (400 m) and high (3.6 km) altitude. The main aim was to test predictions about the relationships betweenfibrinoid deposits and either the volume of intervillous space or the surface area of (intermediate + terminal) villi. Fields of view on Masson trichrome-stained paraffin sections were selected as part of a systematic sampling design which randomised section location and orientation. Relative and absolute volumes were estimated by test point counting and surfaces by intersection counting. Apparent differences were tested by analyses of variance and relationships by correlation and regression analysis. Fibrinoid volume increased during gestation and correlated positively with intervillous volume and villous surface area. However, relative to intervillous volume, themain increase in fibrinoid occurred towards term (36-41 weeks). At high altitude, placentas contained more intervillous space but less fibrinoid. At both altitudes, there were significant correlations between fibrinoid volume and villous surface area. In all cases, changes in fibrinoid volume were commensurate with changes in villous surface area. Whilst findings lend support to the notion that fibrinoid deposition during normal gestation is influenced by the quality of vascular perfusion, they also emphasise that the extent of the villous surface is a more generally important factor. The villous surface may influence the steady state between coagulation and fibrinolysis since some pro-coagulatory events operate at the trophoblastic epithelium. They occur notably at sites of trophoblast de-epithelialisation and these arise following trauma or during the extrusion phase of normal epithelial turnover.
Keywords: Fibrin; Placenta; Horionske resice, vzorčenje; Chemistry; Analysis; Slika, obdelava z računalnikom; Chorionic Villi Sampling; Gestacijska starost; Image Processing, Computer-Assisted; Histološke tehnike; Nosečnost; human pregnancy; Pregnancy; Organ, teža; Gestational Age; histologija; Organ Weight; organi; Histological Techniques; stereologija